Uma leitura do património através de uma revista de arquitectura do primeiro quartel do século XX - de Morais Da Mesquita, Marieta (DISEGNARECON, 2008)
This article proposes to present the project “Paper Architecture”, a research about A Construcção Moderna, the first specialized Portuguese magazine in the fields of architecture and engineering. Published in Lisbon between 1900 and 1919. This illustrated magazine constitutes a primary source for studying the processes of architectural representation in the first quarter of the 20th century. In that sense the magazine A Construcção Moderna is viewed as an essential instrument for the analysis and interpretation of the Portuguese architectural legacy.